2005
DOI: 10.1523/jneurosci.1910-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Nucleus Lesions Enhance the Psychomotor-Activating, Incentive Motivational, and Neurobiological Effects of Cocaine

Abstract: The subthalamic nucleus (STN) is traditionally thought to be involved in motor control, and dysfunction of the STN is thought to contribute to movement disorders. Here, we show that the STN also plays an important role in motivational processes and the response to drugs of abuse. Specifically, bilateral STN lesions produced a dose-dependent increase in the psychomotor-activating effects of cocaine, the rate at which animals acquired cocaine self-administration, and the motivation for cocaine assessed using a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 63 publications
6
35
3
Order By: Relevance
“…Support for this view comes from experiments in which lesions of the subthalamic nucleus, which have been shown to enhance motivation for both food and drugs of abuse, enhance sign-tracking to visual cues paired with these rewards (Baunez et al 2002;Uslaner et al 2005Uslaner et al , 2008. In the present experiments, however, amphetamine exposure, which has motivation-enhancing effects similar to those of subthalamic nucleus lesions (Ferrario and Robinson 2007;Mendez et al 2007;Nordquist et al 2007), had the opposite effect on sign-tracking.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Support for this view comes from experiments in which lesions of the subthalamic nucleus, which have been shown to enhance motivation for both food and drugs of abuse, enhance sign-tracking to visual cues paired with these rewards (Baunez et al 2002;Uslaner et al 2005Uslaner et al , 2008. In the present experiments, however, amphetamine exposure, which has motivation-enhancing effects similar to those of subthalamic nucleus lesions (Ferrario and Robinson 2007;Mendez et al 2007;Nordquist et al 2007), had the opposite effect on sign-tracking.…”
Section: Discussionsupporting
confidence: 51%
“…6 Locomotor activity in amphetamine-exposed and saline control rats in experiment 2 (in 5-min bins) during a 15-min pre-drug baseline period (bins 1-3) and 30 min (bins 4-9) after an amphetamine challenge injection (2 mg/kg, i.p.) subthalamic nucleus, which appear to similarly enhance incentive salience, increase sign-tracking behavior (Uslaner et al 2005(Uslaner et al , 2008. The present experiments, however, show that a regimen of amphetamine exposure which induced locomotor sensitization and which has been shown in other settings to enhance incentive salience attribution (Harmer and Phillips 1998;Mendez et al 2007) caused a decrease in sign-tracking (contact with the CS), while at the same time causing an increase in goal-tracking (approach to the site of reward delivery during the CS).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Indeed, bilateral STN lesions enhance the motivation for food, whereas decreasing the motivation for cocaine (Baunez et al, 2002. Although Baunez et al (2002Baunez et al ( , 2005 demonstrate that STN lesion enhance the motivation for cocaine, Uslaner et al (2005) show an opposite result . But the basal cocaine intake of both control and lesioned rats in the Uslaner et al (2005) study is so low, that no possible decrease could have been observed and it might well be possible that the potentiation observed after STN lesions on the progressive ratio performance has more to do with acquisition than with motivation for the drug itself.…”
Section: Discussionmentioning
confidence: 96%
“…For example, deep brain stimulation of the STN for the treatment of Parkinson's disease (Limousin et al, 1998;Charles et al, 2002;Welter et al, 2002), which is thought to inactivate the STN (Benazzouz et al, 1993(Benazzouz et al, , 1995(Benazzouz et al, , 2000Lozano et al, 2002), produces non-motoric side-effects, including compulsive gambling (Lu et al, 2006;Smeding et al, 2007), increased desire for levadopa treatment Schupbach et al, 2005), and an increased disposition for addiction (Funkiewiez et al, 2003). Consistent with this, preclinical studies have shown that bilateral STN lesions increase motivation for both food (Baunez et al, 2002) and cocaine (Uslaner et al, 2005), as measured by progressive ratio responding, and increase impulsive responding for a food reward, which could be indicative of enhanced motivation (Baunez et al, 1995;Baunez and Robbins, 1997;Phillips and Brown, 1999;Florio et al, 2001;.…”
Section: Introductionmentioning
confidence: 88%